Implementasi Metode Skrip Kooperatif Melalui Pemanfaatan Media “Ape’ dalam Meningkatkan Prestasi Belajar Mahasiswa - Endah Hendarwati; Vega Hesmatantya (Universitas Trunojoyo Madura, 2016)
The learning activities are carried Lecturer influence on student learning outcomes. Student learning outcomes PG PAUD during is still lacking, one possible cause of lectures is not utilize the media. The media is indispensable in the learning of the students, because it is very influential on student results. Students PG PAUD forwards are required to create and use a variety of media in teaching Early Childhood. Lectures by the media using APE is helping students to be aware of all kinds, benefits and how to use and create media in early childhood play activities. Given the importance of the use of media to Students PG PAUD, this research is focused on improving student learning outcomes using APE media through Cooperative Script method, especially on subjects Playing Games Early Childhood.Research using classroom action research. Classroom action research is a form of action research conducted in the classroom with the aim of improving the learning process. Subjects in this study were students PG PAUD UmSurabaya Semester 2. The data obtained from the study then used as the innovation of faculty to improve student achievement and create an atmosphere that fosters learning motivation lecture to students.